Strategies for improving the pedaling technique - Duc, S.; Bertucci, W.; Grappe, F. (The Journal of Sports Medicine and Physical Fitness, 2019)
INTRODUCTION: Pedaling technique which can be defined as the way the cyclists pedal, has been mostly studied in lab conditions from pedal force kinetic, joints kinematic, and/or muscular activity patterns because it is considered as a main factor for gross efficiency (GE). Although this method is much controversial, its quality has extensively been evaluated from the index of pedal force effectiveness (IFE), i.e. the ratio between the effective to the total pedal force. Over the last thirty years, preferred pedaling technique has been compared between the experienced cyclists and non-cyclists and also often been manipulated by instructing these subjects to improve their effective force production during the downstroke phase ("pushing"), the upstroke phase ("pulling-up") or around top and bottom dead centers ("circling"). EVIDENCE ACQUISITION: It has been shown that PREF pedaling technique is much repeatable across crank cycles in experienced cyclists than in novice cyclists. PULL involves a significant increase of IFE compared to PREF, mainly attributed to the increase of the muscular work of hip (RF) and knee flexors muscles (BF) during the upstroke. This improvement is larger in non-cyclists than in experienced cyclists but it can be optimized in the latter after a short-term training (2-4 weeks) with pedal force feedback or uncoupled cranks. EVIDENCE SYNTHESIS: Despite that PULL enhances a lower muscular recruitment of contralateral knee extensors, GE and cycling performance variables are not significantly increased, probably due to the reversal effect of training with normal cranks and the highly robust pedaling technique of experienced cyclists. The question arises, as to whether or not, changes in pedaling technique can improve cycling efficiency if enough time is given for cyclists to adapt to a new pedaling technique. CONCLUSIONS: Further studies should investigate the pedaling techniques in more "ecological" conditions, as there is not probably one but several pedaling techniques that could optimize cycling efficiency according to the pedaling conditions (time-trial, uphill, road, off-road and track cycling), and should also focus on the potential effects of long-term training of PULL pedaling technique on cycling efficiency and cycling performance.